Law and justice on the small screen - Robson, Peter 1947-; Silbey, Jessica (Hart Pub, 2012)
This is a wide-ranging collection of essays about law in and on television. In light of the book's innovative taxonomy of the field and its international reach, it will make a novel contribution to the scholarly literature about law and popular culture.